Rachel. - Grimké, Angelina Weld (Oberon Books, 2014)
"Rachel is a young, educated, middle-class woman. But she is born into an African-American family in the early 20th century--a world in which ignorance and violence prevail. While her family and neighbours find different ways to survive, Rachel's dreams of getting married and becoming a mother collide with the tragic events of her family's past as she confronts the harsh reality of a racist world. Written exactly midway between the American Civil War and the end of slavery, and the explosion of Civil Rights in the 1960s, this hauntingly beautiful and profoundly shocking play still asks urgent questions for today."--Back cover.